A new methodology for costing wound care. Issue 6 (13th December 2012) - Harding, Keith; Posnett, John; Vowden, Katherine
<x xml:space="preserve">Abstract</x> Increasing pressure on health care budgets highlights the need for clinicians to understand the true costs of wound care, in order to be able to defend services against indiscriminate cost cutting. Our aim was to develop and test a straightforward method of measuring treatment costs, which is feasible in routine practice. The method was tested in a prospective study of leg ulcer patients attending three specialist clinics in the UK. A set of ulcer‐related health state descriptors were defined on the basis that they represented distinct and clinically relevant descriptions of wound condition ['healed', 'progressing'; 'static''deteriorating; 'severe' (ulcer with serious complications)]. A standardised data‐collection instrument was used to record information for all patients attending the clinic during the study period regarding (i) the health state of the ulcer; (ii) treatment received during the clinic visit and (iii) treatment planned between clinic visits. Information on resource use was used to estimate weekly treatment costs by ulcer state. Information was collected at 827 independent weekly observations from the three study centres. Treatment costs increased markedly with ulcer severity: an ulcer which was 'deteriorating' or 'severe' cost between twice and six times as much per week as an ulcer which was progressing normally towards healing. Higher costs were driven primarily by more frequent clinic visits and by the costs of hospitalisation for ulcers with severe complications. This exercise has demonstrated that the proposed methodology is easy to apply, and produces information which is of value in monitoring healing and in potentially reducing treatment costs.